PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN PARIWISATA DI PANTAI PANDAWA, DESA KUTUH, KUTA SELATAN, BADUNG - Andryano Febrian Bambar; I Putu Anom (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2016)
Pandawa Beach is one of destination in Bali that be popular and much visited by tourists. Therefore, it is necessary managed by Kutuh Village community well. This study discussed about community participation in tourism development in Pandawa Beach. The method of this study is in-depth interviews, observation and literature study. In determining the informant, the technique that used is purposive sampling. Data analysis used qualitative descriptive. Result from this study is Kutuh Village community participation in decision making.The type of community participation in making decissin is interactive, in tourism program planning ( in tourism facilities development that are self mobilization, in tourism investments that are self mobilization, and in tourism promotion that is intensive ), in sharing profit from tourism activity in Pandawa Beach, and the type of community participation in sharing profit is self mobilization.